Detecting northern peatland vegetation patterns at ultra‐high spatial resolution. Issue 4 (17th December 2019) - Räsänen, Aleksi; Aurela, Mika; Juutinen, Sari; Kumpula, Timo; Lohila, Annalea; Penttilä, Timo; Virtanen, Tarmo
Abstract: Within northern peatlands, landscape elements such as vegetation and topography are spatially heterogenic from ultra‐high (centimeter level) to coarse scale. In addition to within‐site spatial heterogeneity, there is evident between‐site heterogeneity, but there is a lack of studies assessing whether different combinations of remotely sensed features and mapping approaches are needed in different types of landscapes. We evaluated the value of different mapping methods and remote sensing datasets and analyzed the kinds of differences present in vegetation patterns and their mappability between three northern boreal peatland landscapes in northern Finland. We utilized field‐inventoried vegetation plots together with spectral, textural, topography and vegetation height remote sensing data from 0.02‐ to 3‐m pixel size. Remote sensing data included true‐color unmanned aerial vehicle images, aerial images with four spectral bands, aerial lidar data and multiple PlanetScope satellite images. We used random forest regressions for tracking plant functional type (PFT) coverage, non‐metric multidimensional scaling ordination axes and fuzzy k‐medoid plant community clusters. PFT regressions had variable performance for different study sites ( R 2 −0.03 to 0.69). Spatial patterns of some spectrally or structurally distinctive PFTs could be predicted relatively well. The first ordination axis represented wetness gradient and was well predicted using remotely sensed data ( R 2 0.64 to 0.82), but the other three axes had a less straightforward explanation and lower mapping performance ( R 2 −0.09 to 0.53). Plant community clusters were predicted most accurately in the sites with clear string‐flark topography but less accurately in the flatter site ( R 2 0.16–0.82). The most important remote sensing features differed between dependent variables and study sites: different topographic, spectral and textural features; and coarse‐scale and fine‐scale datasets were the most important in different tasks. We suggest that multiple different mapping approaches should be tested and several remote sensing datasets used when maps of vegetation are produced. Abstract : Vegetation patterns in northern peatlands are spatially heterogenic from ultra‐high to coarse scale; there is also evident between‐site heterogeneity but absent comparisons between sites. We used random forest regressions for tracking plant functional type (PFT) coverage, ordination axes, and fuzzy plant community clusters in three different northern boreal peatland landscapes in northern Finland. We utilized field‐inventoried vegetation plots together with spectral, textural, topography, and vegetation height remote sensing data from unmanned aerial vehicle, airborne and satellite platforms from 0.02‐ to 3‐m pixel size. PFT regressions had variable performance for different study sites. The first ordination axis represented wetness gradient and was well predicted; the other three axes had a less straightforward explanation and lower mapping performance. Plant community clusters were predicted most accurately in the sites with clear string‐flark topography but less accurately in the flatter site. The most important remote sensing features differed between dependent variables and study sites.